Fenomena Adaptasi Beragama di Saat Pandemi Covid-19 Oleh Umat Hindu di Desa Bangsongan Kecamatan Kayen Kidul Kabupaten Kediri Ditinjau dengan Teori Yang Sakral dan Yang Profan Perspektif Mircea Eliade - Damayanti, Syifa Salsabila (UIN Sunan Kalijaga Yogyakarta, 2022)
This article attempts to explain changes in the religious community, taking place during the Covid-19 pandemic. To control the spread of the virus, the government issued a ban on not performing worship in houses of worships. The research focus is on the religious adoption by Hindus in Bangsongan village of Papar Kediri Regency, aiming to reveal how the Hindu community adapted to that ruling.